Identification of Fungal Pathogens in Otomycosis and Their Drug Sensitivity: Our Experience - Ali, Khaled; Hamed, Mahmood A.; Hassan, Hameda; Esmail, Amira; Sheneef, Abeer (International Archives of Otorhinolaryngology, 2018)
Introduction Otomycosis is a common problem in otolaryngology practice. However, we usually encounter some difficulties in its treatment because many patients show resistance to antifungal agents, and present high recurrence rate.Objectives To determine the fungal pathogens that cause otomycosis as well as their susceptibility to the commonly used antifungal agents. Additionally, to discover the main reasons for antifungal resistance.Methods We conducted an experimental descriptive study on 122 patients clinically diagnosed with otomycosis from April 2016 to April 2017. Aural discharge specimens were collected for direct microscopic examination and fungal culture. In vitro antifungal susceptibility testing was performed against the commonly used antifungal drugs. We tested the isolated fungi for their enzymatic activity.Results Positive fungal infection was found in 102 samples. The most common fungal pathogens were Aspergillus and Candida species, with Aspergillus niger being the predominant isolate (51%). The antifungal susceptibility testing showed that mold isolates had the highest sensitivity to voriconazole (93.48%), while the highest resistance was to fluconazole (100%). For yeast, the highest sensitivity was to nystatin (88.24%), followed by amphotericin B (82.35%), and the highest resistance was to terbinafine (100%), followed by Itraconazole (94.12%). Filamentous fungi expressed a high enzymatic ability, making them more virulent.Conclusion The Aspergillus and Candida species are the most common fungal isolates in otomycosis. Voriconazole and Nystatin are the medications of choice for the treatment of otomycosis in our community. The high virulence of fungal pathogens is owed to their high enzymatic activity. Empirical use of antifungals should be discouraged.
Keywords: otomycosis; yeast; aspergillus; antifungal agents; candida; dermatophytes